(untitled) (Orfeu, 2024)
Motivation and engagement are top-ics of interest in various theoretical and empirical studies. In this regard, this text aims to discuss the relationship between motivation and engagement in music practice, teaching, and learning contexts. For this purpose, the concepts of motiva-tion and engagement are reviewed, as well as the flow theory as a way of relating the discussed topics in the text. The literature review highlights the dynamic interaction between motivation and engagement, as the motivation that led to action can be sustained through the individual’s engage-ment in the activity. Furthermore, motiva-tional and engagement processes can be qualified to the point of leading individuals to a flow experience. This text also pro-vides a review of some empirical studies on motivation and engagement across differ-ent music practice, teaching, and learning contexts, bridging theoretical aspects with empirical research possibilities and appli-cations in teaching and learning processes